2020
DOI: 10.1001/jamanetworkopen.2019.20745
|View full text |Cite
|
Sign up to set email alerts
|

Association of Subclinical Hypothyroidism and Cardiovascular Disease With Mortality

Abstract: IMPORTANCE Subclinical hypothyroidism is a common clinical entity among US adults associated in some studies with an increase in the risk of cardiovascular disease (CVD) and mortality. However, the extent to which CVD mediates the association between elevated serum thyrotropin (TSH) and mortality has not yet been well established or sufficiently quantified. OBJECTIVE To elucidate the extent to which subclinical hypothyroidism, elevated serum TSH and normal serum free thyroxine, or high-normal TSH concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(98 citation statements)
references
References 40 publications
7
81
1
9
Order By: Relevance
“…Our analysis suggests a possible mechanism linking TSH to cardiovascular complications, which is a sensible alternative to the thyroid failure hypothesis by other authors (16). It also well accounts for the U-shaped relationship between TSH concentration and cardiovascular risk, as elsewhere described (14,15).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our analysis suggests a possible mechanism linking TSH to cardiovascular complications, which is a sensible alternative to the thyroid failure hypothesis by other authors (16). It also well accounts for the U-shaped relationship between TSH concentration and cardiovascular risk, as elsewhere described (14,15).…”
Section: Discussionsupporting
confidence: 83%
“…While increased and high-normal free thyroxine (FT4) concentration is a well-established risk factor for malignant arrhythmia and sudden cardiac death (6,7), the association between thyrotropin (TSH) concentration and cardiovascular mortality is less well understood (8)(9)(10)(11). Studies reported either no relation at all (12,13) or a rather complex Ushaped association (14,15), as has been shown in a recent population study based on the large NHANES datasets (16). Likewise, a recent study observed elevated FT4 concentration in stress cardiomyopathy or Takotsubo syndrome (17).…”
Section: Introductionmentioning
confidence: 99%
“…Another large pooled analysis of over 31,900 participants, also done by the Thyroid Studies Collaboration, found that the increased risk of coronary heart disease events in those with SCH did not vary by serum TPO antibody status (P for interaction = 0.65) (40). SCH has also been associated with all-cause mortality, mediated by CVD, in a study that used data from the National Health and Nutrition Examination Survey in the United States (41).…”
Section: Associations Between Sch and Cvdmentioning
confidence: 99%
“…En el estudio se encontró con mayor frecuencia el SM en pacientes con hipotiroidismo subclínico, así como mutualidad entre ambas. Se sabe que existe una asociación entre los niveles elevados de TSH y la enfermedad cardiovascular, así como que el SM conlleva mayor riesgo cardiovascular por daño endotelial 20,21 . En un estudio realizado por Razvi, se demostró que regular los niveles de TSH con levotiroxina en pacientes con hipotiroidismo subclínico estaba asociado a la disminución de eventos cardiovasculares 22 .…”
Section: Discussionunclassified